USING MODERN AND INNOVATIVE METHODS AND ARTIFICIAL INTELLIGENCE IN TEACHING THE ‘ELECTRICITY AND MAGNETISM’ SECTIONS IN SPECIALIZED EDUCATIONAL INSTITUTIONS (Multidisciplinary Journal of Science and Technology, 2026)
This study explores the use of modern and innovative teaching methods, as well as artificial intelligence technologies, in teaching the “Electricity and Magnetism” sections in specialized educational institutions. The research highlights the importance of interactive pedagogical approaches, digital educational resources, virtual laboratories, simulations, and AI-based learning tools in improving students’ understanding of complex physical concepts. The integration of artificial intelligence into the educational process enables personalized learning, increases students’ motivation, and enhances problem-solving and analytical skills. Furthermore, the study discusses the effectiveness of innovative methodologies in developing critical thinking, independent learning, and practical competencies among students. The results demonstrate that the application of modern technologies and AI significantly improves the quality and efficiency of physics education, particularly in the teaching of electricity and magnetism topics.